(untitled) (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. Our research novelty was the validation of the use of the method of Ultrasound Imaging to measure the changes in the size of the cross-sectional area (CSA) of the multifidus muscle, performing exercises for lumbar stability. Stabilization exercises have been designed in order to enhance the neuromuscular control system correct the dysfunction. Research aim. The purpose of this study was to establish the effect of core stability exercise for cross-sectional area of lumbar multifidus muscle and physical capacity for elderly women. Research methods. The elderly women (n = 22) were in occupations involving light or no manual work and did not take part in sports. CSA of the multifidus muscle was measured from L2 to L5 vertebral segments. These measures were taken with ultrasound „TITAN TM ” (SonoSite, USA). For the assessment of physical capacity we estimated the women’s static strength endurance of back muscles and dynamic strength endurance of abdominal muscles. The tests were done three times: the first testing occurred before exercises for training lumbar stability, the second – after four months, and the third – after eight months of applying exercises for training lumbar stability. Research results. The results of study showed that after eight months of stability exercises, the subjects had significantly larger right side multifidus CSA than before practice – 9.01 ± 1.1, the left side of the lumbar multifidus muscle was 8.23 ± 0.9 (p < 0.05). After the evaluation of physical capacity we revealed that after eight moths it was 97.6 ± 2.8 s (very good), compared to the values before the research (25.4 ± 9.2) (p < 0.05). Discussion and conclusions. After the core stabilization exercise program multifidus CSA values were significantly larger than before practice, multifidus muscle asymmetry decreased. Physical activity programs adapted to the elderly women increased their physical capacities. Keywords: lumbar stability, physical activity programs, age.